Research progress on peptides that inhibit melanin synthesis - Yu, Binrui; Wang, Nailong; Cai, Shanshan; Yan, Hao; Sun, Shaojia; Wang, Siru; Li, Ye; Liang, Zhengting (Frontiers in Pharmacology, 2025)
Melanin produced by melanocytes, primarily determines human skin color and protects against ultraviolet radiation. However, excessive melanin deposition can lead to skin conditions such as freckles, age spots, and moles, potentially causing aesthetic concerns and psychological distress. Consequently, there is significant research interest in developing safe and effective whitening products that inhibit melanin synthesis. Bioactive peptides represent a promising compound category that effectively reduces melanin synthesis with minimal side effects. This review explores melanin pigmentation, identifies sources of peptides that inhibit melanin synthesis, and elucidates the mechanisms by which these peptides operate, aiming to contribute to developing novel whitening products.